Maintaining Roads : The Argentine Experience with Output-Based Contracts - Liautaud, Gerard (World Bank, Washington, DC, 2012)
The Argentine government is using output-based contracts with the private sector for rehabilitation and maintenance of its nonconcessioned road network. The multiyear lump sum contracts, funded by the government, specify required road service outputs and use incentive-based payment schedules to ensure the quality of the work. After three years of operation the 60 contracts (averaging US$10 million) in the first phase are working well. By 2002 around 75 percent of Argentina's nonconcessional roads should be operating under output-based contracts.